Training and Assistance in the Development of Islamic Values Integrated Assessment Instruments for Madrasah Teachers - Ade Haerullah; Said Hasan; Jassia I. Pagala; M Nur Kadir (Peneliti.net, 2022)
The cause of learning problems in madrasas is the dualism between religious science and general science. This learning practice produces graduates who are not balanced between intellectual and spiritual aspects. The integration of Islamic values ​​during the learning process is expected to be a solution to the dualism of learning. The purpose of this community service activity (PKM) in the form of training and mentoring is to provide knowledge and improve the competence of MTs Sahabat Cendikia teachers as partner schools to develop an integrated assessment instrument for Islamic values ​​that is equipped with its rubric. The methods used are lectures, participatory training and assignments. The subjects involved were 18 teachers of MTs SC in Ternate. Process data and activity results were analyzed descriptively. The results of the PKM activity data analysis showed that the teacher's response to this activity was very good, this was indicated by the high level of participation of participants in attendance as much as 100%, completing and presenting the task of preparing an integrated assessment instrument for Islamic values ​​with good value of 88.9%. Thus, it can be concluded that community service activities through this training and mentoring can solve the problems experienced by partners.